Sex Education for Adolescents in Islamic View: A systematic Literature Review - Anita Juliya; Zahrotun Nada (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
The problem of adolescents is increasing every year. There are various kinds of adolescent problems, but this article specifically aims to describe sex education from an Islamic perspective. The conclusion of this study is that sex education for adolescents in an Islamic perspective is very important to be implemented and implemented by parents, teachers, and other educators both at home and at school. Because with sex education, teenagers will be able to reduce the occurrence of sexual deviations that often occur among teenagers. This sex education does not teach about how to have sex between the opposite sex, especially to teenagers, but is part of preventive efforts in preventing deviations that occur among teenagers, including sexual deviations.